Evaluation of fungal-specific fluorescent labeled echinocandin probes as diagnostic adjuncts - Pratt, Ayiasha (2013)
The diagnosis of invasive fungal infections from radiographic imaging is non-specific and problematic. As a first step toward increasing specificity, we describe the development of a broad-spectrum fungal-specific targeting molecule, which when modified with a fluorescent label fully retains its targeting properties, and provides a basis for future imaging applications.